Interfacial Charge Modulation: An Efficient Strategy for Boosting Spatial Charge Separation on Semiconductor Photocatalysts. Issue 13 (14th February 2019) - Tao, Xiaoping; Gao, Yuying; Wang, Shengyang; Wang, Xiaoyu; Liu, Yang; Zhao, Yue; Fan, Fengtao; Dupuis, Michel; Li, Rengui; Li, Can
Abstract: Surface modulation via injection or extraction of charge carriers in microelectric devices has been used to tune the energy band alignment for desired electrical and optical properties, yet not well recognized in photocatalysis field. Here, taking semiconductor bismuth tantalum oxyhalides (Bi4 TaO8 X) as examples, chemically inactive molybdenum oxide (MoO3 ) with a large work function is introduced to qualitatively tune the properties of interfacial charges, achieving an evidently enhanced upward band bending and intensive built‐in electric field. Such a simple charge modulation exhibits a remarkable improvement in photocatalytic water oxidation, reaching an apparent quantum efficiency of 25% at the input wavelength of 420 nm. The validity and generality of surface charge modulating strategy are further demonstrated using other semiconductors (e.g., C3 N4 ) and decorators (e.g., V2 O5 ). The findings not only provide a promising strategy for rationally manipulating the interfacial built‐in electric field in photocatalysis but also pave the way to learn from microelectronic technologies to construct artificial photosynthesis systems for solar energy conversion. Abstract : Molybdenum oxide (MoO3 ) is introduced as a surface modification on Bi4 TaO8 X (X = Cl, Br) to tune the interfacial charges, achieving an enhanced upward band bending as well as an intensive built‐in electric field. Such charge modulation results in an evident improvement in photocatalytic water oxidation under visible light irradiation, reaching an apparent quantum efficiency of 25% at 420 nm.